Flatting amongst LGBTIQ+ people in Aotearoa New Zealand - Brodie Fraser; Mary Buchanan (Kōtuitui, 2025)
Flatting, or shared housing, is become an increasingly common living arrangement in Aotearoa New Zealand. Despite this, there remains a limited body of research about flatting, particularly in how it impacts marginalised groups. This paper provides a quantitative description of the characteristics and housing experiences of LGBTIQ+ people who flat in Aotearoa, and make comparisons to LGBTIQ+ people who are not flatting. Flatters were more likely to be younger, identify as queer, and earn lower incomes than non-flatters. Furthermore, they were more likely to have needed to move due to a poor relationship with someone in the household, were more likely to have experienced any housing discrimination, and were more likely to be worried about housing discrimination. Our data shows flatting is a site of vulnerability for LGBTIQ+ people, opening them up to discrimination within the home, which has implications for their safety and security of tenure. Increased research and policy are needed to protect the rights and safety of flatters, particularly those from the LGBTIQ+ community.